Codex apocryphus gnosticus Novi Testamenti Band 2: Briefe und Apokalypsen aus den Schriften von Nag Hammadi und dem Codex Tchacos mit einer Neuausgabe der »Epistula Apostolorum«. Koptisch und deutsch - Nagel, Peter (Mohr Siebeck, 2023)
Volume 2 follows the first one on Gospels and Acts by offering the Coptic text and German translation of three pseudapostolic letters and two apocalypses with introductions and annotations. For the first time since Carl Schmidts Editio princeps in 1919, the Coptic-Akhmimic text of the Epistula Apostolorum is edited anew with a structured German translation and linguistic indices.
PublicationDate: 20230524
Keywords: Gnosis -- Neutestamentliche Apokryphen -- koptisch -- Fallbuch -- Editionen, Textausgaben -- Neues Testament